Application of the Problem-Solving Method to Improve Critical Thinking Abilities in Social Studies Learning for Elementary School Students - Syafruddin, Syafruddin; Syamsiah, Syamsiah; Nadiatun, Nadiatun; Rosdiana, Rosdiana (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Teaching, one of which is the problem solving learning mein Social studies learning in elementary schools places more emphasis on social sciences in studying social phenomena and problems that occur in society. Problems that occur today are that there are still many arguments that social studies learning is rote learning. However, in reality from social studies learning there are phenomena that can be explored by students, so that students can find real problems in the environment to use as learning and can improve students' ability to think critically in responding to these problems. Optimal development of critical thinking skills requires interactive classes. In order for learning to be interactive, the learning design must be attractive so that students can be actively involved in the learning process. Learning that develops critical thinking skills involves students as thinkers, not as someone being taught. The teacher acts as a mediator, facilitator and motivator who helps students in learning and not tthod where through the Problem Solving method it is hoped that it can facilitate understanding of the subject matter provided and later can improve the quality of the learning process which can then improve students' critical thinking in social studies learning. This research aims to analyze the application of the problem solving method to improve critical thinking abilities in elementary school students' social studies learning. The method used in this research is the literature study method. The results of the research show that the application of the Problem Solving learning method emphasizes students' ability to solve a problem. In this way, students' critical thinking skills will continue to be trained.